Analysis of Eurasian Stone curlew (Burhinus oedicnemus) microbial flora reveals the presence of multi-drug resistant pathogens in agro-pastoral areas of Sicily (Italy). Issue 10 (October 2020) - Foti, Maria; Grasso, Rosario; Fisichella, Vittorio; Mascetti, Antonietta; Zafarana, Manuel Andrea; Colnaghi, Marco; Grasso, Maria; Spena, Maria Teresa
Abstract: Spread of multi-drug resistant (MDR) bacteria in natural environments pose a risk to human and animal health. Wild birds are considered to be reservoirs of human pathogens and vectors of antimicrobial resistance distribution in the environment. The aim of this study is to assess the occurrence of antibiotic resistant bacteria in isolates from bird specimens living in three agro-pastoral areas of the southeastern Sicily. We analyzed the microbiomes of the Eurasian Stone curlew Burhinus oedicnemus (Charadriiformes, Aves) and identified 91 Gram positive and 212 Gram negative strains, whose antimicrobial susceptibility to 11 and 9 antibiotic classes (respectively) was evaluated using agar disk diffusion test. Isolates showed significant levels of antimicrobial resistance, and a high percentage of MDR strains was found both between the Gram positive (49.4%) and the Gram negative (34.9%). Multi-drug resistance levels are higher among strains isolated in the beak and the eye than among enteric (faeces and cloaca) strains. Our results indicate high levels of MDR strains among wild bird populations, with a potential threat to wildlife and human populations. Abstract : Microbiology; Environmental science; Environmental health; Epidemiology; Infectious disease; Bacteriology; Antibiotic resistant bacteria; Disk diffusion antimicrobial tests; Drug resistance; Gram negative bacteria; Gram positive bacteria; Burhinus oedicnemus ; Sicily